A. \(3{e^3} + 1 \le m < 3{e^4} + 1\).
B. \(m \ge 3{e^4} + 1\).
C. \(3{e^2} + 1 \le m \le 3{e^3} + 1\).
D. \(m < 3{e^2} + 1\).
B
·\(y' = {\left( {\frac{4}{{2017}}} \right)^{{e^{3x}} - \left( {m - 1} \right){e^x} + 1}}.\ln \left( {\frac{4}{{2017}}} \right).{\left( {{e^{3x}} - \left( {m - 1} \right){e^x} + 1} \right)^\prime }\)=\(y' = {\left( {\frac{4}{{2017}}} \right)^{{e^{3x}} - \left( {m - 1} \right){e^x} + 1}}.\ln \left( {\frac{4}{{2017}}} \right).\left( {3{e^{3x}} - \left( {m - 1} \right){e^x}} \right)\)
·Hàm số đồng biến trên khoảng \(\left( {1;\,2} \right)\) Û
\(y' = {\left( {\frac{4}{{2017}}} \right)^{{e^{3x}} - \left( {m - 1} \right){e^x} + 1}}.\ln \left( {\frac{4}{{2017}}} \right).\left( {3{e^{3x}} - \left( {m - 1} \right){e^x}} \right) \ge 0,\,\forall x \in \left( {1;\,2} \right)\)(*), mà \(\left\{ \begin{array}{l}{\left( {\frac{4}{{2017}}} \right)^{{e^{3x}} - \left( {m - 1} \right){e^x} + 1}} > 0\,,\,\forall x \in \mathbb{R}\\\ln \left( {\frac{4}{{2017}}} \right) < 0\end{array} \right.\). Nên (*) Û \(3{e^{3x}} - \left( {m - 1} \right){e^x} \le 0,\,\forall x \in \left( {1;\,2} \right)\) Û \(3{e^{2x}} + 1 \le m,\,\forall x \in \left( {1;\,2} \right)\)
· Đặt \(g\left( x \right) = 3{e^{2x}} + 1\,,\,\forall x \in \left( {1;\,2} \right)\), \(g\left( x \right) = 3{e^{2x}}.2 > 0\,,\,\forall x \in \left( {1;\,2} \right)\)
Vậy (*) xảy ra khi \(m \ge g\left( 2 \right)\) Û \(m \ge 3{e^4} + 1\).
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247